Using Model 7-C Protocol in Analyzing Factors Affecting Implementation Corruption Prevention Program in the Regional Tax Revenue Sector - Rieza Adhitya Bintana; Ima Mayasari (PERSPEKTIF, 2023)
This paper aims to analyze the factors that influence the implementation of the corruption prevention program by the Corruption Eradication Commission (KPK) in the local tax revenue sector. In order to approach this problem, the theoretical reference from the 7-C Protocol analysis model from Cloete (2018) is used. Qualitative data were collected through interviews and documentation studies from activity reports, research results, and media news, which were analyzed using a post-positivism approach and descriptive analytical research methods. The unit of analysis is the implementer of the corruption prevention program in the regional tax revenue sector, namely the Prevention Task Force at the KPK Coordination and Supervision Directorate (Korsupgah KPK). This study concludes that to find out the factors that influence the implementation of corruption prevention programs in the local tax revenue sector implemented by Korsupgah KPK can be analyzed using the 7-C Protocol analysis model from Cloete (2018) which consists of the variables Content, Context, Commitment, Capacity, Client/Coalition, Communication, and Coordination.